Minimally invasive nephrectomy for inflammatory renal disease (2019)
Objective: Once chronic inflammatory renal disease (IRD) develops, it creates a severe peri-fibrotic process, which makes it a relative contraindication for minimally invasive surgery (MIS). Our objective is to show that laparoscopic nephrectomy (LN) is a surgical option in IRD with fewer complications and better outcomes. Methods: Retrospective review of patients who underwent a modified-surgical laparoscopic transperitoneal nephrectomy was performed. Data search included all operated patients between May 2013 and May 2018 that had a pathology result with any renal inflammatory condition (xanthogranulomatous pyelonephritis, chronic nephritis, and renal tuberculosis). We describe intra-operative variables such as operative time, blood loss, conversion rate, postoperative complications and length of hospital stay. Results: There were 51 patients who underwent laparoscopic nephrectomy with a confirmatory pathology report for IRD. We identified four (8%) major complications; three of them required transfusion and one conversion to open surgery. The mean operative time was 233±108 min. Mean estimated blood loss was 206±242 mL excluding the conversion cases and 281±423 mL including them. The mean length of hospital stay was 3.0±2.0 days. Conclusion: Laparoscopic nephrectomy for IRD can safely be done. It is a reproducible technique with low risks and complication rates. Our experience supports that releasing the kidney first and leaving the hilum for the end is a safe approach when vascular structures are embedded into a single block of inflammatory and scar tissue.